Frequency of Plasmid-Mediated Quinolone-Resistance (qnr) Genes in Pseudomonas aeruginosa Strains Isolated from Hospitalized Patients - Hamid Reza Goli; Sayede Fateme Moradi; Mohammad Reza Haghshenas; Ghazaleh Elahi; Mehrdad Gholami (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Quinolones and fluoroquinolones are used to treat infection with resistant strains of Pseudomonas aeruginosa; however, the inappropriate use of antibiotics regardless of resistance patterns has led to the emergence of new and resistant strains. To address this concern, we conducted a study to investigate the frequency of plasmid-mediated quinolone-resistance (qnr) genes among P. aeruginosa isolates collected from the educational hospitals in Sari. Materials and methods: In this cross-sectional study, 100 clinical isolates of P. aeruginosa were collected from hospitalized patients. The bacterial isolates were recognized through standard microbiological tests. Antimicrobial susceptibility was determined by the disk diffusion method, following Clinical and Laboratory Standards Institute (CLSI) guidelines. Polymerase chain reaction (PCR) was performed to detect qnrA, qnrB, and qnrS genes. Data analysis was performed using SPSS statistical software version 22, and the Chi-square test was applied. Results: In total, 100 P. aeruginosa strains were isolated from patients. Of these, 71 strains were isolated from male patients. The majority of isolates were collected from ICU patients. Among the studied genes, the prevalence rates of qnrA, qnrB, and qnrS were 31%, 24%, and 35%, respectively. Conclusion: Our study highlights the widespread distribution of qnr genes, particularly qnrS, among P. aeruginosa clinical isolates in Sari. The highest antibiotic sensitivity was observed for piperacillin/tazobactam, indicating it as the most effective treatment option. Among quinolones, ciprofloxacin demonstrated the best efficacy against tested isolates. Given the high prevalence of plasmid-mediated quinolone-resistance genes (PMQR), regular screening of P. aeruginosa isolates for PMQR genes is essential to prevent the dissemination of resistant strains. Future studies focusing on molecular mechanisms of resistance and interventions to curb its spread are highly recommended.